1980
DOI: 10.1139/f80-072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metals on the Biomass Production Kinetics of Freshwater Copepods

Abstract: The effects of cadmium, copper, mercury, lead, and arsenic on the growth and mortality rates of a natural assemblage of copepods using natural food and water were determined. A seasonal cycle in toxicity was observed for all the metals except arsenic. Lead toxicity appeared to be related to the ash-free dry weight of the seston, but the reason for the variation in toxicity of cadmium, copper, and mercury remain unknown. The chronic toxicity of some metals differs much less between copepods and daphnids than do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Of the various responses, those that best reflect individual performance and are most easily related to Borgmann et al (1980) showed that, in general, toxicity was accurately indicated by a drop in growth rate. In earthworms, the attainment of maturity is indicated by the clitella development.…”
Section: Growth and Reproduction (Noec And Ec 50 )mentioning
confidence: 99%
“…Of the various responses, those that best reflect individual performance and are most easily related to Borgmann et al (1980) showed that, in general, toxicity was accurately indicated by a drop in growth rate. In earthworms, the attainment of maturity is indicated by the clitella development.…”
Section: Growth and Reproduction (Noec And Ec 50 )mentioning
confidence: 99%
“…Uma complicação adicional resulta quando o As (III) é lentamente oxidado em As (V) em condições ricas em oxigênio, que geralmente são empregadas nos testes de toxicidade aquáticos. É geralmente aceito que o As (III) é mais tóxico do que o As (V), uma hipótese apoiada por estudos com invertebrados de água doce (Borgmann et al, 1980;Spehar e Fiandt, 1986;Golding et al, 1997). Assim, é possível que o As possa causar a toxicidade observada neste estudo.…”
Section: Testes De Toxicidade Aguda Com C Dúbia E Avaliação E Identiunclassified
“…Jlg/L de mercúrio reduzem significativamente a sobrevivência de copépodos em ambientes naturais (BORGMANN et a/., 1980). No caso do chumbo, ocorre maior Entre os organismos de ambientes aquáticos ma1s utilizados na avaliação de substâncias tóxicas e poluentes estão as algas, o zooplâncton e os peiXes.…”
Section: Niunclassified